Effect of offensive rebound on the game outcome during the 2019 Basketball World Cup - Koutsouridis, C.; Lioutas, D.; Galazoulas, C.; Karamousalidis, G.; Stavropoulos, N. (Journal of Physical Education and Sport, 2020)
The offensive rebound (OR) is particularly important because it offers a second opportunity to score against a misplaced defense, and it is a performance indicator that distinguishes the winning teams in playoff games. This research was conducted to investigate the effectiveness of offensive plays following an offensive rebound, both from winners and losers. The secondary aim was to compare and analyze factors that could have an impact on the effectiveness of offensive plays following an OR. The sample size consisted of 28 basketball games from the World Basketball Cup, which was held in China (2019). For statistical analysis of the variables, we used frequency analysis, crosstabulation analysis with Chi2 (Chi-square) test (significance level set at p<0.05), adjusted standardized residual and CHAID decision trees. The results indicated that each team was awarded ~10.3 ORs per game, and more than 7 out of 10 ORs were recovered in the paint. Furthermore, teams thatultimately lost the game executed more offensive plays during the first 5 s after their OR than teams that won the game (p=0.035). At the same time, teams that lost the game had more unsuccessful offensive plays after the OR with no statistically significant difference. Regarding the effectiveness of the offense following an OR, individual actions were found to be more effective than organized plays (p=0.01). In addition, plays that were executed during the first 5 s after the OR were more efficient in contrast with plays that lasted more seconds (p=0.003). These findings indicate the importance of the OR in the game and can be used by basketball coaches who want to optimize their coaching plan.